(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Attitude and Knowledge of Farmers and Income of Porang Farmer (Amorphophallus Muelleri) in Mundeh Kauh Village, West Selemadeg District, Tabanan Regency. Indonesia is known as an agricultural country which means a country that relies on the agricultural sector both in livelihood and supporting development. One of the agricultural sectors is plantations. Porang has recently become a crop that has been discussed since the Minister of Agriculture exported 60 tons of this crop commodity to China. In addition, this commodity is also exported to countries such as Japan, Vietnam, Thailand, Hong Kong, Malaysia, South Korea, Zealand, Italy, and Pakistan. However, the need for this commodity has not been f ulfilled optimally because porang plants have not been intensively cultivated by porang farmers in Bali. In addition, it is also caused because porang farmers do not have enough attitude and knowledge to cultivate porang plants. The purpose of this study is to determine the attitude and knowledge of farmers towards porangfarming and to know the amount of income generated by porang farming. The methods used in this study are qualitative analysis and quantitative analysis. The results showed that (1) Porang farmers in Mundeh Kauh Village, West Selemadeg District, Tabanan Regency had a positive attitude and excellent knowledge of porang cultivation techniques and (2) Porang farming income in Mundeh Kauh Village, West Selemadeg District, Tabanan Regency amounted to Rp. 17.584.424,17/ha/years. Farmers must improve land processing and the application of basic fertilizers in order to achieve maximum cultivation results and farmers must more often attend trainings carried out by relevant stakeholders.